2020
DOI: 10.3390/cells9122685
|View full text |Cite
|
Sign up to set email alerts
|

The Role of BAR Proteins and the Glycocalyx in Brain Endothelium Transcytosis

Abstract: Within the brain, endothelial cells lining the blood vessels meticulously coordinate the transport of nutrients, energy metabolites and other macromolecules essential in maintaining an appropriate activity of the brain. While small molecules are pumped across specialised molecular transporters, large macromolecular cargos are shuttled from one side to the other through membrane-bound carriers formed by endocytosis on one side, trafficked to the other side and released by exocytosis. Such a process is collectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 129 publications
(195 reference statements)
0
13
0
Order By: Relevance
“…Lectin has a high binding affinity for glycoprotein N-acetylglucosamines and has been used to identify the glycocalyx composition. 40 We show that the HDF cell line saturates at lower lectin concentrations than FaDu and THP-1, indicating the presence of more sugars in the glycocalyx. In Figure 5b we use the experimental values from Figure 1a to fix the N CD81 , N CD36 , and N SRB1 for the three different cell lines, to estimate the effect of the Psome radius and the degree of polymerization N PC on the binding energy.…”
Section: ■ Results and Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Lectin has a high binding affinity for glycoprotein N-acetylglucosamines and has been used to identify the glycocalyx composition. 40 We show that the HDF cell line saturates at lower lectin concentrations than FaDu and THP-1, indicating the presence of more sugars in the glycocalyx. In Figure 5b we use the experimental values from Figure 1a to fix the N CD81 , N CD36 , and N SRB1 for the three different cell lines, to estimate the effect of the Psome radius and the degree of polymerization N PC on the binding energy.…”
Section: ■ Results and Discussionmentioning
confidence: 68%
“…We characterize the differences in cell glycocalyx through lectin-binding assay (Figure a). Lectin has a high binding affinity for glycoprotein N-acetylglucosamines and has been used to identify the glycocalyx composition . We show that the HDF cell line saturates at lower lectin concentrations than FaDu and THP-1, indicating the presence of more sugars in the glycocalyx.…”
Section: Resultsmentioning
confidence: 81%
“…Accordingly, heterogeneity in adhesion molecule glycosylation has been suggested as a vascular and disease-specific molecular zip code for inflammatory responses 59 . It has also been suggested that the glycocalyx may play an important role in transcytosis at the BBB 60 . Despite the established importance of the BBB glycocalyx, the discovery and development of BBB-targeting reagents recognizing BBB glyco-epitopes has been under-pursued, perhaps because of the suboptimal glyco-recognition of Ig-based binding scaffolds that have been used in BBB screens 18 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of f-actin in “membrane shaping” is key to cellular processes such as transcytosis, cell division, filopodial protrusions and NT formation [ 31 , 34 , 36 ]. The formation of membranous structures is endorsed by the role of regulators of membrane curvature, which is a family of proteins that comprises the crescent-shaped Bin/Amphiphysin/Rvs (BAR) domain [ 68 ].…”
Section: Nomenclature Clarifying Morphological Structuresmentioning
confidence: 99%